Memories of revolt : the 1936-1939 rebellion and the Palestinian national past - Swedenburg, Ted (University of Arkansas Press, 2003)
Swedenburg's book, based largely on research in the Israeli-occupied West Bank and Gaza in the mid-1980s, is an exploration of the ways in which veterans of the 1936-39 Palestinian revolt against British colonial rule and the Zionist project it protected, remember that historical event.